2007
DOI: 10.1007/s10350-007-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Distribution of Colorectal Cancer in Barbados: 1985-2004

Abstract: There has been a steady increase in both right-sided and left-sided colonic cancers without gender predilection. The increase in early-stage tumors and reduction in emergency presentations during the latter part of the study suggests value in instituting a formal national colonoscopic screening program to assess its prospective effect on these parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…the demographic distribution was also predictable with a peak in the 6th to 8th decades of life. this matches the age distribution for invasive CrC in the Caribbean literature (8)(9)(10)(11)(12)(13). However, it is notable that 7% of patients with neoplastic polyps were <49 years of age.…”
Section: Characteristicsupporting
confidence: 85%
See 1 more Smart Citation
“…the demographic distribution was also predictable with a peak in the 6th to 8th decades of life. this matches the age distribution for invasive CrC in the Caribbean literature (8)(9)(10)(11)(12)(13). However, it is notable that 7% of patients with neoplastic polyps were <49 years of age.…”
Section: Characteristicsupporting
confidence: 85%
“…Previous studies have documented a 'right shift' in the Jamaican population (8)(9)(10) and in other Caribbean territories (11)(12)(13), where CrC primaries have become more prevalent in the right colon. therefore, it was predictable that the precursor neoplastic polyps were most prevalent in the right colon in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These data have significant implications on the present study, as it was shown that the predominant pattern was right-sided disease in 44.3% of Barbadian patients. In a previous study, Zbar et al (7) also reported a significant right-sided shift over two decades in Barbadian patients, without a decline in left-sided primaries. A right-shift was also observed in other Caribbean nations, with McFarlane et al (13) reporting right-sided lesions in 28.5% of Jamaican patients and Joachim et al (16) reporting right-sided lesions in 26.3% of patients in Martinique.…”
Section: Discussionmentioning
confidence: 81%
“…International data indicate that males have significantly more cancer-related deaths than females (9,10) and a significantly lower overall survival (9,11,12). Of note, the other Caribbean islands have reported different patterns, with published data from Jamaica (13,14), Trinidad and Tobago (15) and an older Barbadian study (7), all reflecting a female predilection. The only other Caribbean nation that reported a male preponderance was Martinique (16).…”
Section: Discussionmentioning
confidence: 99%
“…The polyp distribution was also expected as similar right-side dominant patterns have been documented in publications from the Caribbean region. [6][7][8] In our study, when screening colonoscopy found CRC, it was still in the early stages, which have a greater probability of cure and better 5-year survival compared to those with locally advanced disease, 9 and more likely to benefit from less invasive laparoscopic colectomy. 10 Most importantly, screening colonoscopy in just under 1 in 4 patients screened that identified neoplastic polyps which could be completely removed to interrupt the adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 92%